Innovation in Making Meatballs, Pempek, and Sate Lilit with Snow Mushrooms (Tremella Fuciformis) - Atmaja, I Made Purwa Dana (Universitas Pendidikan Indonesia, 2021)
Snow mushrooms are typically served directly, such as sautÃ©ed or fried with flour coating. More variations on the snow mushrooms-based food is expected to provide new experiences for people who want to enjoy mushrooms with the home flavor foods, particularly for people who do not eat meat. The purpose of this study is to determine the outcomes of the innovation of meatballs, pempek, and sate lilit with snow mushrooms as the basic ingredients. The snow mushrooms were processed as the basic ingredients for making meatballs, pempek, and satay. The foods were evaluated by 25 trained panelists: Culinary Department lecturers and students, in terms of their aromas, textures, colors, and tastes. Panelists were given a checklist to assess the results of the observations, which were then scored using a Likert scale to determine whether the quality of the meatball, pempek, and sate lilit were very good, good, quite good, not good, or very bad. The experiment was carried out in the kitchen of Politeknik Pariwisata Bali. Based on the results of experiments and organoleptic assessments, it can be seen that the innovation of meatballs, pempek, and sate lilit yields very good results, with an average percentage of 80% for meatballs, 83% for pempek, and 80% for sate lilit.